DOI: 10.18174/453958
|View full text |Cite
|
Sign up to set email alerts
|

Clever and cool : generating design guidelines for climate-responsive urban green infrastructure

Abstract: Clever and cool Generating design guidelines for climate responsive urban green infrastructure Wiebke Klemm Wiebke Klemm Clever and cool Generating design guidelines for climate-responsive urban green infrastructure, 292 pages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 122 publications
(482 reference statements)
0
5
0
Order By: Relevance
“…Regarding the introduction of vegetation, while their cooling effects are widely described in the literature (e.g., Dihkan et al, 2021; Klemm, 2018; Schlaepfer et al, 2020), employing vegetation in informal areas in hot arid climates comes with challenges. First, planting trees and shrubs might be largely conditioned or even impaired in narrow street profiles due to lack of space.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the introduction of vegetation, while their cooling effects are widely described in the literature (e.g., Dihkan et al, 2021; Klemm, 2018; Schlaepfer et al, 2020), employing vegetation in informal areas in hot arid climates comes with challenges. First, planting trees and shrubs might be largely conditioned or even impaired in narrow street profiles due to lack of space.…”
Section: Discussionmentioning
confidence: 99%
“…1): adapting urban materials (increasing albedo values and/or changing specific heat properties of surfacing materials), implementing shade (blocking direct solar radiation by implementing artificial shading structures), and introducing vegetation (provision of cooling through shading and evapotranspiration). These are cooling strategies widely validated by previous studies (e.g., Klemm, 2018;Lenzholzer, 2015;Tsoka, 2017;Cortesão et al, 2020). The interventions were assessed regarding their capacity to reduce short-and longwave radiation and air temperature, regulate ventilation, and increase evaporative cooling.…”
Section: Data Compilationmentioning
confidence: 99%
“…The buffer zones in between are valuable. In her study, Klemm [71] reported that 20% of people preferred to stay at the edge between sunlit and shaded conditions. According to the previous consideration, no indication of the species used are provided; instead, some guidelines for the selection of typologies of vegetation are given.…”
Section: The New Master Planmentioning
confidence: 97%
“…Most studies have focused on the green designs of public squares and their microclimatic influences during a hot summer's day to compare the thermal comfort values [10,15,16], others have explored the climate change adaptation potential in landscape architectural designs [17], whilst others have analyzed the diverse thermal performances of several urban squares with varying morphological and green characteristics [18,19]. Only a few studies, however, have balanced both summer and winter conditions [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%